An Investigation into the Injury Incidence and Training Habits of Group Fitness Instructors via a Retrospective Database Analysis - Hastings, Bryce (Auckland University of Technology, 2018)
Introduction. Les Mills International distributes group fitness classes to over 18,000 fitness facilities worldwide. These classes are taught by over 130,000 group fitness instructors. These instructors are required to simultaneously coach and demonstrate each class physically at a high level. Previous studies have demonstrated significant injury risk for instructors and participants when undertaking group fitness programs. As yet the specific injury risks and factors contributing to these injuries for Les Mills instructors is unknown. Purpose. To investigate the relationship between age, training history and incidence and intensity of pain and injury in the spine and lower limb in Les Mills group fitness instructors via retrospective data analysis. Method. Three thousand two hundred and eight Les Mills instructors completed a retrospective online survey, providing details on regional pain, training history and intensity of injury over a six month period. The sample was made up of 2614 females and 594 males. Results. Training volume was associated with the reporting of any pain in female participants with those in moderate training volume categories being at most risk. The age of instructors had a significant relationship with the recording of any pain and specifically lower limb pain in females with older groups recording less pain. Older participants also had a lower intensity of injury in the male group. Regular core training resulted in reduced odds of reporting spinal and lumbar pain in females while increasing the likelihood of reporting knee pain in males. Undertaking regular flexibility training increased the odds of reporting spinal, lumbar, hip and lower limb pain in females and males. Strength training increased the odds of reporting lumbar and spinal pain in males. Undertaking high impact programs on a regular basis increased the likelihood of reporting knee and lower leg pain in females and males. The frequency of participating in regular bodybalance classes was associated with the intensity of injuries in females while age, frequency of bodypump classes and regular strength training effected the intensity of injuries in males. Conclusions. These findings highlight risks and benefits of teaching and participating in various types of group fitness classes and adopting various training practises outside of group fitness in Les Mills instructors. These factors should be taken into consideration when instructors organise their weekly teaching and training schedules.
Keywords: Group fitness; Injuries; Training; Exercise